Time-resolved luminescence Z-scan of CsI using power femtosecond laser pulses. (May 2019) - Belsky, A.; Fedorov, N.; Gridin, S.; Gektin, A.; Martin, P.; Spassky, D.; Vasil'ev, A.
Abstract: Time-resolved Z-scan technique gives the opportunity to obtain consistent data for dependence of the yield and decay kinetics from excitation density. The excitation by 4th harmonics of femtosecond Ti:Sapphire laser (6.2 eV) allows to measure with wide dynamical range of excitation density (from 10 17 to 10 22 excitations per cubic centimeter) CsI luminescence. In the density range 10 18 -10 19  cm −3 the yield of 310 nm band (fast intrinsic luminescence) increases linearly with energy of the laser pulse, and yield of 430 nm band decreases inversely. In the same density range the subnanosecond decay of 310 nm band becomes slower and in microsecond kinetics of 430 nm band increases the contribution of nanosecond components. Highlights: Excitation density dependence of 4.1 eV band of CsI luminescence is superlinear for low intensities. Z-scan technique is applied for study of 2.9 and 4.1 eV emissions of CsI. Excitation density dependence of decay kinetics for 2.9 and 4.1 eV emissions of CsI is studied.